ANALYSIS OF COMPANY INTERNAL CONTROL IN THE OCCURRENCE OF FRAUD AT DELTA ARTHA SIDOARJO PEOPLE'S CREDIT BANK (BPR) - Devina Yulia Gunita; Imelda Dian Rahmawati (International Journal of Business, Law and Political Science, 2025)
Objective: The purpose of this study is to determine how the company's internal control system prevents fraud, as well as whether the implementation of the company's internal controls is running effectively for the company. Method: This study uses a data analysis method, namely descriptive qualitative method. The data collection techniques applied in this study are as follows: 1) Interviews, 2) Observation, 3) Documentation, 4) Triangulation. The population in this study is the heads of operational divisions and LPN, and internal auditors at BPR Delta Artha bank. Result: The results of this study indicate that the company's internal control at BPR Delta Artha Sidoarjo is running well. The company establishes strict policies/regulations, conducts periodic checks, and provides strong data protection to enhance security. Novelty: The benefits of this research are expected to serve as a model for internal control in the banking sector.